2019
DOI: 10.1111/cdev.13291
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations of Identity Processing Styles With Prodiversity and Proequality Values in Adolescence

Abstract: In adolescence, the formation of personal identity and values may be intertwined, since values are among the main issues considered when building one's identity. This study examined how sociocognitive strategies used in the process of identity formation were related with adoption of prodiversity and proequality values, which are critically important for socially diverse contemporary societies. Participants were 916 adolescents (51.4% females, M age = 15.65, SD age = 0.73 at baseline) involved in a three-wave l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
(100 reference statements)
1
6
0
1
Order By: Relevance
“…These findings confirm our hypothesis about the key role played by thoughtful exploration and are in line with previous research on identity processes (Crocetti et al, 2010(Crocetti et al, , 2012Hatano et al, 2016) and styles (Crocetti et al, 2014;Erentaitė et al, 2019;Soenens et al, 2005), which highlighted the associations between in-depth exploration and multiple personal (e.g., openness to experience; Crocetti et al, 2010;Hatano et al, 2016) and social (e.g., civic engagement; Crocetti et al, 2012) aspects that inform individuals' views of others within society (Brandt et al, 2015;Pancer et al, 2007). Besides extending the literature on associations between personal identity processes and social identity processes (Albarello et al, 2018), our findings also highlight for the first time the link between in-depth exploration and ethnic prejudice among late adolescents.…”
Section: Fighting Prejudice: the Protective Role Of Educational Identitysupporting
confidence: 93%
See 1 more Smart Citation
“…These findings confirm our hypothesis about the key role played by thoughtful exploration and are in line with previous research on identity processes (Crocetti et al, 2010(Crocetti et al, , 2012Hatano et al, 2016) and styles (Crocetti et al, 2014;Erentaitė et al, 2019;Soenens et al, 2005), which highlighted the associations between in-depth exploration and multiple personal (e.g., openness to experience; Crocetti et al, 2010;Hatano et al, 2016) and social (e.g., civic engagement; Crocetti et al, 2012) aspects that inform individuals' views of others within society (Brandt et al, 2015;Pancer et al, 2007). Besides extending the literature on associations between personal identity processes and social identity processes (Albarello et al, 2018), our findings also highlight for the first time the link between in-depth exploration and ethnic prejudice among late adolescents.…”
Section: Fighting Prejudice: the Protective Role Of Educational Identitysupporting
confidence: 93%
“…Moreover, in-depth exploration is a core feature (Crocetti et al, 2013; Zimmermann et al, 2012) of the information-oriented identity style and, as previously mentioned, high levels of exploration of educational identity commitments have shown to be associated with the adolescents’ adoption of this style (Negru-Subtirica et al, 2017). In turn, this style was found to be positively associated with pro-diversity and pro-equality values (Erentaitė et al, 2019) and civic engagement (Crocetti, Erentaitė et al, 2014), and negatively associated with forms of closure to experiences or others, such as the need for cognitive closure (Crocetti et al, 2009). Additionally, late adolescents who adopt an information-oriented style endorsed less traditional or conservative opinions, showing lower need for closure, right-wing authoritarianism, and cultural conservatism (Soenens et al, 2005).…”
Section: Antecedents Of Prejudice: the Importance Of Identity Processesmentioning
confidence: 99%
“…Moreover, in-depth exploration of identity in the educational domain is also conceived as a core feature ( Zimmermann et al, 2012 ; Crocetti et al, 2013 ) of the information-oriented identity style ( Berzonsky, 1989 ), whereby individuals actively seek and process relevant information to make accurate and thoughtful decisions ( Berzonsky, 1989 ) in contrast to superficial information processing. Importantly, this style was found to be positively associated with pro-diversity and pro-equality values ( Erentaitė et al, 2019 ) and civic engagement ( Crocetti et al, 2014 ), and negatively associated with forms of closure to experiences or others, such as the need for cognitive closure ( Crocetti et al, 2009 ) and different forms of prejudice (i.e., racism and xenophobia; Soenens et al, 2005 ). It has been shown that adolescents who adopt such an information-oriented identity style also have a high degree of cognitive complexity and employ a vigilant and systematic processing style in decisional situations ( Berzonsky and Ferrari, 1996 ); thus, it can be assumed that they are also less susceptible to use social cognitive simplifications that lead to social prejudice ( Allport, 1954 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature [ 35 , 36 , 37 ] the temporal perspective may have implications with respect to psychosocial functioning. In this sense, the way in which individuals use temporal frames to define their own, goals, ideals, life projects may contribute to identity construction.…”
Section: Introductionmentioning
confidence: 99%